Implementasi Pojok Literasi Sebagai Strategi Penigkatan Literasi Siswa di Lingkungan SDN 1 Tongka Kalimantan Tengah - Nor Hayat; Sondra Swestyani; Tri Yani Oktavia; Dila Asmianur; Widia Astuti; Yandi Novia; M. Hilman Rahmantara (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This community service program was implemented to address the low literacy levels among students in remote areas of Central Kalimantan, specifically at SDN 1 Tongka, Gunung Timang District, North Barito Regency. The main objective of the program was to implement a literacy corner as a strategy to improve student literacy and create a sustainable literacy ecosystem in the school environment. The method used included participatory and adaptive approaches, applying the concept of a "mobile literacy corner" adapted to the limitations of local space and resources. The program was carried out over 45 days, covering preparation, implementation, and evaluation phases. The results showed a significant increase in students' reading interest, with a 68% rise in the frequency of visits to the literacy corner. Pre-test and post-test evaluations indicated an average increase in students' literacy skills of 27%, particularly in reading comprehension and vocabulary mastery. Participatory observation revealed the formation of a stronger literacy culture in the school environment, characterized by student-initiated literacy discussions and increased use of references in academic tasks. The program also successfully developed an adaptive and contextual model for implementing literacy corners, which has the potential to be replicated in other remote areas of Indonesia.